(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2019)
The aim of the work was to assess the level of sustainable development in Poland and selected European Union countries. The time range of analyzes is 2004 and 2015. The research was based on data published by the Central Statistical Office. The synthetic indicator was used in the research. Based on selected indicators, selected countries were divided into three classes with different levels of sustainable development. During the period under review, slight changes in the places of countries in individual classes illustrating the level of sustainable development were noticed.